Boundary shear flow past a cylinder near a wall. (November 2019) - Chen, L.F.; Wu, G.X.
Abstract: An investigation on boundary shear flow past a circular cylinder near a wall is numerically performed via a stabilized finite element method. The main focus is to uncover its major difference with the flows corresponding to the symmetry boundary, and to two identical circular cylinders in a side-by-side arrangement. In particular at Reynolds number R e = 100, extensive simulations are made for different gaps between the cylinder and wall. It is noted that in the wake of the cylinder the vortex contour lines shift upwards. At R e = 100, the flow behind a cylinder near the wall may be time dependent. With a reduction of the gap spacing to a magnitude in (0.75, 1), the vortex shedding nearly vanishes. For the flow behind two identical circular cylinders side and side, the flow may change from periodic flow to totally irregular one. The drag force CD, lift force C L, rms and Strouhal number St of the circular cylinder near the wall vary differently with the gap, compared with those in the other two cases. When the cylinder is located in the boundary layer, the boundary shear flow has strong effect on the hydrodynamic quantities. Extensive simulations are also made for R e = 200, 400, 600 and 800. It is found that the Reynolds number has strong effect on the flow and force on the cylinder, not only through the variation of Re itself but also the boundary layer of the wall. Withe Re increasing, strong vortex shedding from the near-wall cylinder at e = 0.5 starts above a Re in (200, 300).